Forest Vegetation : Inventory and Management Recommendations, Outer Island, Apostle Islands National Lakeshore, Wisconsin - Fraundorf, William J. (University of Wisconsin-Stevens Point, College of Natural Resources, 1984)
The Apostle Islands National Lakeshore (AINL), Wisconsin, was established as a unit of the National Park System on 26 September 1970 (PL 91-424). Since the establishment of the AINL, the development of resource management policies has been the focus of concern. Existing AINL natural resource management policies (PL 91-424, AINL Master Plan of 1971, AINL Statement for Management of 1977, AINL Environmental Assessment of 1981, AINL Selected Management Alternatives of 1982) are conceptual in nature and are in reference to the Park as a whole. The major goal of AINL natural resource management policy is the re-establishment of the original (ca. 1880) conditions of the Lakeshores resources for the purpose of visitor exposure to the same. The next step to be taken toward the attainment of the above goal is the development 11of detailed working plans for the key (major) natural resources of the AINL" (Brander 1981). The objective of this thesis was to inventory, and develop "detailed working plans" (management recommendations) for, the forest vegetation of Outer Island. Eight Major vegetation-types were identified on Outer Island. The forest vegetation-types were quantitatively sampled and comparisons were made with original forest vegetation conditions to determine which forest species needed to be actively managed in the attempt to re-establish original forest conditions on Outer Island. Original and current forest vegetation comparisons identified hemlock (Tsuga canadensis), yellow birch (Betula alleghaniensis), white pine (Pinus strobus) and red pine (Pinus resinosa) as the "target species" of management activities facilitating re-establishment of original forest conditions. The eight vegetation-types previously identified were mapped in greater detail for the purpose of identifying areas on Outer Island believed to be environmentally suitable to the regeneration of the target species listed above•. Management recommendations to facilitate the reproduction of hemlock and yellow birch involve increasing the availability of seedbeds within environmentally appropriate conditions. Management recommendations to facilitate the reproduction of white pine and red pine include the removal of competing vegetation, seedbed preparation and planting.